‘Monte Carlo’ Simulation Predicting on the Movement of Investments – During the Covid Pandemic in Indonesia - Azis, Musdalifah; Ilmi, Zainal; Hakim, Yundi Permadi; Qodri, Muhammad; Darma, Dio Caisar (Department of Management, Faculty of Economics and Business, Universitas Negeri Semarang, 2021)
The movement of the net asset value (NAV) of mutual fund products (MFP) whether high or low in the Covid-19 pandemic conditions in 2020. With the support of the Monte Carlo Simulation (MCS), this study intends to predict the rate of return on mutual fund investment (MFI) providing a choice of the average demand for return on mutual funds (MFR) that investors need. Analysis of the prediction of NAV movements and the rate of return on MFI in 55 MFP with a trial frequency of 48 times, we get an estimate of the average demand for MFR of 37 out of 100 cumulative numbers of probability distributions. The result is 77.08 percent, and an estimated average MFR in Indonesia during the 2020 Covid-19, the simulation got was IDR 421,954. The contribution resulted in a vital discovery of NAV in Indonesia in response to the economic recession affected by Covid-19..